Microsoft SQL server 2008 reporting services : step by step - Misner, Stacia (Step by step (Redmond, Wash.), 2009)
Teach yourself how to build, manage, and access SQL Server 2008 reports one step at a time. Whether you re a report developer, IT administrator, or business user, this sequential, learn-by-doing tutorial shows you how to deliver the business intelligence information your organization needs. Discover how to: Install and configure Reporting Services Put Report Builder and Report Designer tools to work Create interactive, online reports that enable users to sort and filter data Add charts and gauges to present data visually Deploy reports to Microsoft Office SharePoint Server Monitor server performance and help secure content Use subscriptions to distribute reports via e-mail Build ad hoc reports and extend them with custom code CD features: Practice exercises and code samples Fully searchable eBook.